2012
DOI: 10.1302/0301-620x.94b1.27690
|View full text |Cite
|
Sign up to set email alerts
|

Use of the reamer–irrigator–aspirator technique to obtain autograft for ankle and hindfoot arthrodesis

Abstract: The use of autograft bone is the best option when undertaking a procedure that requires bone graft because it is osteogenic, osteoconductive and osseo-inductive. Pain, morbidity and complications associated with harvesting iliac or non-iliac sites occur in between 6% and 30% of cases. An alternative source of graft with possibly a lower morbidity is the intramedullary canal. In this study, 28 patients undergoing 30 arthrodesis procedures on the hindfoot had a mean of 48 cm(3) (43 to 50) of bone harvested local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Autologous bone grafting has received a negative reputation in the past, mainly due to the high risk of postoperative complications related to the harvesting procedure [6]. However, more recent innovative and minimally invasive harvesting techniques have mitigated the historic issue of donor site morbidity and renewed the interest in autologous bone as a preferred source for bone grafting [7-9]. …”
Section: Introductionmentioning
confidence: 99%
“…Autologous bone grafting has received a negative reputation in the past, mainly due to the high risk of postoperative complications related to the harvesting procedure [6]. However, more recent innovative and minimally invasive harvesting techniques have mitigated the historic issue of donor site morbidity and renewed the interest in autologous bone as a preferred source for bone grafting [7-9]. …”
Section: Introductionmentioning
confidence: 99%
“…The effluent collected using RIA also contains many osteogenic growth factors, 4,15,16 and the filter system can provide large volumes of bone graft. 17 Although RIA has been used clinically, 18 there is no evidence to suggest that these cells remain viable. Therefore the questions raised are, is the apparent clinical success related to the growth factors or due to the osteogenic cells?…”
mentioning
confidence: 99%
“…Numerous studies have shown that RIA can provide good quality and quantity of autologous bone graft with relatively little post-operative pain [6][7][8] Table 1 [4,5,9,[10][11][12][13][14][15][16][17]. Most reported complications were seen when the intact femur was used as source of harvesting autologous bone graft.…”
Section: Discussionmentioning
confidence: 99%